Fabrication and characterization of hybrid polymer solar cell / Toong Way Yun - Toong, Way Yun (2012)
The easy fabrication method, tunable physical and chemical properties and cost-effective fabrication process, makes organic solar cells (OSC) very attractive in photovoltaic application. Nonetheless, the device performance is limited due to the low charge mobility of the organic semiconductors that results in a less efficient of charge transport to the respective electrodes. In order to address such problems, hybrid polymer solar cells based on bulk heterojunction (BHJ) structure, which composed of a combination of both organic and inorganic semiconductors are employed. However, the BHJ device performances are strongly dependent on good processing conditions, especially enhancement of photons absorption as well as the improvement of charge transport properties. Hence, the involved parameters and properties should be well optimized. This dissertation describes the study of effects of blend composition and types of acceptor materials used on the optical, structural, morphological as well as the electrical properties of the three different hybrid BHJ systems. The hybrid materials consist of a blend of p-type conjugated polymer of poly(3-hexylthiophene) (P3HT) and n-type inorganic metal oxide nanoparticles, namely, zinc oxide (ZnO), titanium dioxide (TiO2) and yttrium oxide (Y2O3). The optical, structural and morphological characterizations of the blend thin films using UV-Visible absorption spectroscopy, X-ray diffraction (XRD) spectroscopy, Atomic Force Microscopy (AFM) and Field-effect Scanning Electron Microscopy (FESEM) are discussed. Furthermore, the co-relation of the thin film property with the device performance is presented. The results show that the device performance has been improved by optimizing the blend composition. This is due to an enhancement in light absorption in broader wavelength regime and improved charge transport through the formation of interpenetrating bicontinous pathway for the holes and electrons to reach the respective electrodes. These results are supported by the observation of the AFM and FESEM images of the increment in RMS roughness and formation of phase separation features in the blends. Besides, the well dispersion of inorganic nanoparticles over P3HT yields a larger interfacial area for charge carrier generation. Among the three hybrid systems investigated, P3HT:ZnO device performs the best with an optimal blend composition of 3% of ZnO nanoparticles in blend. In order to further improve the device performances, ZnO sol-gel synthesis route has been utilized to produce a better mixing blend of P3HT and ZnO. Additionally, several approaches have been employed, namely modifying the sol content in blends, varying the annealing temperature, and inserting an additional ZnO buffer layer between the active layer and cathode. An optimal annealing treatment offers improved optical absorption properties and more uniform film surface morphology with eliminated redundant large pores and grain agglomerations. The role of the ZnO buffer layer in the blend system can be seen as an agent in facilitating the electron collection from the active layer to the cathode. The results indicate that the device efficiency has been improved by about 5 times for P3HT:ZnO sol gel device with optimized sol content (0.1ml sol), annealed at an optimized temperature of 100°C with additional ZnO buffer layer, compared to the P3HT:ZnO nanoparticles-based device.